Resolving ambiguous direction of arrival of weak meteor radar trail echoes (Institutet för rymdfysik, 2020)
Ett kort segment av data från SGO's SKiYMET systemet (meteor spår radar) som tidigare samplats in under en meteor-skur, men inte gjorts allmänt tillgänglig, valdes ut som grund för studien om ambiguitets problemet för infallsvinkeln av radar ekon. Det här data settet innehåller mätdata av meteor spår från Sodankylä Geophysical Observatory SKiYMET radarn. "ME20181213_0010.zip" Filen innehåller rå-data från bekräftade spår ekon och hör till en specifik rad av "mp20181213_sodankyla.mpd" filen. zip filen innehåller också en PDF med beskrivning av datan. Utöver detta finns också analys resultaten i "ANALYSIS.zip" filen. I denna fil ligger en "README.txt" fil som beskriver datan. A short segment of data from the SGO SKiYMET system (meteor trail radar) that has previously been collected during a meteor shower, but not made public, was chosen as a basis for the study of ambiguous echo direction of arrival. This data set includes measurement data of meteor trail echoes from the Sodankylä Geophysical Observatory SKiYMET radar. "ME20181213_0010.zip" File contains the raw data from confirmed trail echoes and each belong to a specific row of the summary output "mp20181213_sodankyla.mpd" file. The zip file also contains a PDF that describes the data. The analys results are also avalible in "ANALYSIS.zip". In this file there is a "README.txt" file that describes the data.